Tracing biomass burning aerosol from South America to Troll Research Station, Antarctica - Fiebig, Markus; Lunder, Chris René; Stohl, Andreas (Geophysical Research Letters, 2009)
The atmospheric observatory at the Norwegian Research Station Troll in Queen Maud Land, Antarctica, holds, since February 2007, the first all-year Antarctic atmospheric aerosol particle number size distribution measurements. These are colocated with measurements of the aerosol absorption and spectral scattering coefficients. In June 2007, this instrument set observed an aerosol whose properties were indicative of a biomass burning aerosol. These properties included two log-normal size distribution modes with median particle diameters of 0.105 μm and 0.36 μm, sharply falling off to smaller and larger sizes, and peaks in scattering and absorption coefficient. With backward plume calculations of the Lagrangian transport model FLEXPART and the MODIS fire activity product, a source-receptor relationship was established between biomass burning events in Central Brazil and the aerosol seen at Troll. This is the first direct evidence that the Antarctic continent is susceptible to emissions from as far north as Southern tropical latitudes.
Keywords: Dronning Maud Land; Troll forskningsstasjon; biomasse; klimatologi; meteorologi; utslipp

Evolution of first-year and second-year snow properties on sea ice in the Weddell Sea during spring-summer transition - Nicolaus, Marcel; Haas, Christian; Willmes, Sascha (Journal of Geophysical Research: Atmospheres, 2009)
Observations of snow properties, superimposed ice, and atmospheric heat fluxes have been performed on first-year and second-year sea ice in the western Weddell Sea, Antarctica. Snow in this region is particular as it does usually survive summer ablation. Measurements were performed during Ice Station Polarstern (ISPOL), a 5-week drift station of the German icebreaker RV Polarstern. Net heat flux to the snowpack was 8 W m−2, causing only 0.1 to 0.2 m of thinning of both snow cover types, thinner first-year and thicker second-year snow. Snow thinning was dominated by compaction and evaporation, whereas melt was of minor importance and occurred only internally at or close to the surface. Characteristic differences between snow on first-year and second-year ice were found in snow thickness, temperature, and stratigraphy. Snow on second-year ice was thicker, colder, denser, and more layered than on first-year ice. Metamorphism and ablation, and thus mass balance, were similar between both regimes, because they depend more on surface heat fluxes and less on underground properties. Ice freeboard was mostly negative, but flooding occurred mainly on first-year ice. Snow and ice interface temperature did not reach the melting point during the observation period. Nevertheless, formation of discontinuous superimposed ice was observed. Color tracer experiments suggest considerable meltwater percolation within the snow, despite below-melting temperatures of lower layers. Strong meridional gradients of snow and sea-ice properties were found in this region. They suggest similar gradients in atmospheric and oceanographic conditions and implicate their importance for melt processes and the location of the summer ice edge.
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; klimatologi; meteorologi; målinger; oseanografi; sjøis; snø; økosystemer

Impacts of the Oceans on Climate Change - Reid, Philip C; Fischer, Astrid C; Lewis-Brown, Emily; Meredith, Michael P; Sparrow, Mike; Andersson, Andreas J; Antia, Avan; Bates, Nicholas R; Bathmann, Ulrich; Beaugrand, Gregory; Brix, Holger; Dye, Stephen; et al. (Advances in Marine Biology, 2009)
The oceans play a key role in climate regulation especially in part buffering (neutralising) the effects of increasing levels of greenhouse gases in the atmosphere and rising global temperatures. This chapter examines how the regulatory processes performed by the oceans alter as a response to climate change and assesses the extent to which positive feedbacks from the ocean may exacerbate climate change. There is clear evidence for rapid change in the oceans. As the main heat store for the world there has been an accelerating change in sea temperatures over the last few decades, which has contributed to rising sea‐level. The oceans are also the main store of carbon dioxide (CO2), and are estimated to have taken up ∼40% of anthropogenic-sourced CO2 from the atmosphere since the beginning of the industrial revolution. A proportion of the carbon uptake is exported via the four ocean ‘carbon pumps’ (Solubility, Biological, Continental Shelf and Carbonate Counter) to the deep ocean reservoir. Increases in sea temperature and changing planktonic systems and ocean currents may lead to a reduction in the uptake of CO2 by the ocean; some evidence suggests a suppression of parts of the marine carbon sink is already underway. While the oceans have buffered climate change through the uptake of CO2 produced by fossil fuel burning this has already had an impact on ocean chemistry through ocean acidification and will continue to do so. Feedbacks to climate change from acidification may result from expected impacts on marine organisms (especially corals and calcareous plankton), ecosystems and biogeochemical cycles. The polar regions of the world are showing the most rapid responses to climate change. As a result of a strong ice–ocean influence, small changes in temperature, salinity and ice cover may trigger large and sudden changes in regional climate with potential downstream feedbacks to the climate of the rest of the world. A warming Arctic Ocean may lead to further releases of the potent greenhouse gas methane from hydrates and permafrost. The Southern Ocean plays a critical role in driving, modifying and regulating global climate change via the carbon cycle and through its impact on adjacent Antarctica. The Antarctic Peninsula has shown some of the most rapid rises in atmospheric and oceanic temperature in the world, with an associated retreat of the majority of glaciers. Parts of the West Antarctic ice sheet are deflating rapidly, very likely due to a change in the flux of oceanic heat to the undersides of the floating ice shelves. The final section on modelling feedbacks from the ocean to climate change identifies limitations and priorities for model development and associated observations. Considering the importance of the oceans to climate change and our limited understanding of climate-related ocean processes, our ability to measure the changes that are taking place are conspicuously inadequate. The chapter highlights the need for a comprehensive, adequately funded and globally extensive ocean observing system to be implemented and sustained as a high priority. Unless feedbacks from the oceans to climate change are adequately included in climate change models, it is possible that the mitigation actions needed to stabilise CO2 and limit temperature rise over the next century will be underestimated.
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer; klimatologi

Asymmetries in the moisture origin of Antarctic precipitation - Sodemann, Harald; Stohl, Andreas (Geophysical Research Letters, 2009)
The seasonality of moisture sources for precipitation in Antarctica is studied with a Lagrangian moisture source diagnostic. Moisture origin for precipitation in Antarctica has strongly asymmetric properties, which are related to the Antarctic topography, seasonal sea ice coverage, and the land/ocean contrasts in the mid-latitudes of the southern hemisphere. The highest altitudes of the East Antarctic ice shield, where major ice cores have been drilled, have mean source latitudes of 45–40°S year-round. This finding contrasts to results from previous Lagrangian studies which detected a more southerly moisture origin due to too short trajectories. Now, results from Lagrangian moisture source diagnostics are consistent with findings from general circulation models with tagged tracers. Thus, both approaches can serve as a common benchmark for the interpretation of moisture source indicators based on stable isotopes, such as deuterium excess, in Antarctic ice cores.
Keywords: Antarktis; klimatologi; meteorologi; nedbør

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Klimagåten Antarktis - Winther, Jan-Gunnar (Gyldendal, 2008)
Keywords: Antarktis; IPY; Sydpolen; ekspedisjoner; internasjonale polarår; isbreer; klimaendringer; klimatologi; polarforskning

How representative is a time series derived from a firn core? A study at a low-accumulation site on the Antarctic plateau - Karlöf, Lars; Winebrenner, Dale P; Percival, Donald B (Journal of Geophysical Research: Earth Surface, 2006)
The acquisition and interpretation of increasingly high-resolution climate data from polar ice and firn cores motivates the question: What is the finest depth or timescale on which measurements on cores arrayed over a given area correlate? We analyze dated depth series of electrical and oxygen isotope measurements from a spatial array of firn cores with 3.5–7 km spacing in Dronning Maud Land, Antarctica, each with a temporal span of approximately 200 years. We use wavelet analysis to decompose the series into components associated with changes of averages on different scales, and thus deduce which scales are dominated by environmental noise, and which may contain a common signal. We find that common signals in electrical records have timescales of approximately 1–3 years. We identify only one electrical signal which rises significantly above the background in our 200-year records, evidently corresponding to the Tambora eruption. Several smaller signals correlate in a few of pairs of cores, one of which may correspond to a known volcanic event, but the others appear to be spurious. We present a simulation-based method for testing the significance of apparent electrical signal correlations, and highlight the importance of accurate relative dating between cores. In the case of oxygen-isotope records, we find, surprisingly, no significant correlation on any scale in the records, for any of the pairs of cores. There is, however, a weak trend toward positive correlation at longer timescales (up to 16 years). Statistical theory for the relevant confidence intervals and the observed statistics of the records permit estimation of the length of a data series necessary to reliably detect a hypothetical correlation equal to that observed. For the highest correlation observed on 16-year scales, core records of about 380 years (approximately 30 m at the Dronning Maud Land site) would be necessary to establish significance.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi; meteorologi; tidsserieanalyse

Ozone profiles in the high-latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)-II: Comparison with other satellite sensors and ozonesondes - Sugita, Takafumi; Nakajima, Hideaki; Yokota, T; Kanzawa, Hiroshi; Gernandt, Hartwig; Herber, A; von der Gathen, P; König-Langlo, Gert; Sato, Kaoru; Dorokhov, Valery; Yushkov, V A; Murayama, Yasuhiro; et al. (Journal of Geophysical Research: Atmospheres, 2006)
A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurately determine their trends. The present paper assesses the quality of ozone data in the version 1.4 retrieval algorithm, through comparisons with results obtained from comprehensive ozonesonde measurements and four satellite-borne solar occultation sensors. In the Northern Hemisphere (NH), the ILAS-II ozone data agree with the other data within ±10% (in terms of the absolute difference divided by its mean value) at altitudes between 11 and 40 km, with the median coincident ILAS-II profiles being systematically up to 10% higher below 20 km and up to 10% lower between 21 and 40 km after screening possible suspicious retrievals. Above 41 km, the negative bias between the NH ILAS-II ozone data and the other data increases with increasing altitude and reaches 30% at 61–65 km. In the Southern Hemisphere, the ILAS-II ozone data agree with the other data within ±10% in the altitude range of 11–60 km, with the median coincident profiles being on average up to 10% higher below 20 km and up to 10% lower above 20 km. Considering the accuracy of the other data used for this comparative study, the version 1.4 ozone data are suitably used for quantitative analyses in the high-latitude stratosphere in both the Northern and Southern Hemisphere and in the lower mesosphere in the Southern Hemisphere.
Keywords: Antarktis; klimatologi; meteorologi; ozonlaget; polarområdene; stratosfæren

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

Accumulation variability over a small area in east Dronning Maud Land, Antarctica, as determined from shallow firn cores and snow pits: some implications for ice-core records - Karlöf, Lars; Isaksson, Elisabeth; Winther, Jan-Gunnar; Gundestrup, Niels; Meijer, Harro A J; Mulvaney, Robert; Pourchet, Michel; Hofstede, Coen; Lappegard, Gaute; Pettersson, Rickard; Van Den Broeke, Michiel; Van De Wal, Roderik S W (Journal of Glaciology, 2005)
We investigate and quantify the variability of snow accumulation rate around a medium-depth firn core (160 m) drilled in east Dronning Maud Land, Antarctica (75°00′ S, 15°00’ E; 3470 m h.a.e. (ellipsoidal height)). We present accumulation data from five snow pits and five shallow (20 m) firn cores distributed within a 3.5–7 km distance, retrieved during the 2000/01 Nordic EPICA (European Project for Ice Coring in Antarctica) traverse. Snow accumulation rates estimated for shorter periods show higher spatial variance than for longer periods. Accumulation variability as recorded from the firn cores and snow pits cannot explain all the variation in the ion and isotope time series; other depositional and post-depositional processes need to be accounted for. Through simple statistical analysis we show that there are differences in sensitivity to these processes between the analyzed species. Oxygen isotopes and sulphate are more conservative in their post-depositional behaviour than the more volatile acids, such as nitrate and to some degree chloride and methanesulphonic acid. We discuss the possible causes for the accumulation variability and the implications for the interpretation of ice-core records.
Keywords: Dronning Maud Land; glasiologi; klimamodeller; klimatologi

Antarctic surface and subsurface snow and ice melt fluxes - Liston, Glen E.; Winther, Jan-Gunnar (Journal of Climate, 2005)
This paper presents modeled surface and subsurface melt fluxes across near-coastal Antarctica. Simulations were performed using a physical-based energy balance model developed in conjunction with detailed field measurements in a mixed snow and blue-ice area of Dronning Maud Land, Antarctica. The model was combined with a satellite-derived map of Antarctic snow and blue-ice areas, 10 yr (1991–2000) of Antarctic meteorological station data, and a high-resolution meteorological distribution model, to provide daily simulated melt values on a 1-km grid covering Antarctica. Model simulations showed that 11.8% and 21.6% of the Antarctic continent experienced surface and subsurface melt, respectively. In addition, the simulations produced 10-yr averaged subsurface meltwater production fluxes of 316.5 and 57.4 km3 yr−1 for snow-covered and blue-ice areas, respectively. The corresponding figures for surface melt were 46.0 and 2.0 km3 yr−1, respectively, thus demonstrating the dominant role of subsurface over surface meltwater production. In total, computed surface and subsurface meltwater production values equal 31 mm yr−1 if evenly distributed over all of Antarctica. While, at any given location, meltwater production rates were highest in blue-ice areas, total annual Antarctic meltwater production was highest for snow-covered areas due to its larger spatial extent. The simulations also showed higher interannual meltwater variations for surface melt than subsurface melt. Since most of the produced meltwater refreezes near where it was produced, the simulated melt has little effect on the Antarctic mass balance. However, the melt contribution is important for the surface energy balance and in modifying surface and near-surface snow and ice properties such as density and grain size.
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

The International Trans-Antarctic Scientific Expedition (ITASE): an overview - Mayewski, Paul Andrew; Frezzotti, Massimo; Bertler, Nancy; Ommen, Tas V. A. N.; Hamilton, Gordon; Jacka, Tim H.; Welch, Brian; Frey, Markus; Dahe, Qin; Jiawen, Ren; Simões, Jefferson; Fily, Michel; et al. (Annals of Glaciology, 2005)
From its original formulation in 1990 the International Trans-Antarctic Scientific Expedition (ITASE) has had as its primary aim the collection and interpretation of a continent-wide array of environmental parameters assembled through the coordinated efforts of scientists from several nations. ITASE offers the ground-based opportunities of traditional-style traverse travel coupled with the modern technology of GPS, crevasse detecting radar, satellite communications and multidisciplinary research. By operating predominantly in the mode of an oversnow traverse, ITASE offers scientists the opportunity to experience the dynamic range of the Antarctic environment. ITASE also offers an important interactive venue for research similar to that afforded by oceanographic research vessels and large polar field camps, without the cost of the former or the lack of mobility of the latter. More importantly, the combination of disciplines represented by ITASE provides a unique, multidimensional (space and time) view of the ice sheet and its history. ITASE has now collected >20 000km of snow radar, recovered more than 240 firn/ice cores (total length 7000 m), remotely penetrated to ~4000m into the ice sheet, and sampled the atmosphere to heights of >20 km.
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; geovitenskap; glasiologi; klimatologi; transantarktiske ekspedisjoner

An Observational Study of the Final Breakdown of the Southern Hemisphere Stratospheric Vortex in 2002 - Orsolini, Yvan J.; Randall, Cora E.; Manney, Gloria L.; Allen, Douglas R. (Journal of the Atmospheric Sciences, 2005)
The 2002 Southern Hemisphere final warming occurred early, following an unusually active winter and the first recorded major warming in the Antarctic. The breakdown of the stratospheric polar vortex in October and November 2002 is examined using new satellite observations from the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument aboard the European Space Agency (ESA) Environment Satellite (ENVISA7-) and meteorological analyses, both high-resolution fields from the European Centre for Medium-Rangc Weather Forecasts and the coarser Met Office analyses. The results derived from MIPAS observations are compared to measurements and inferences from well-validated solar occultation satellite instruments [Halogen Occultation Experiment (HALOE), Polar Ozone and Aerosol Measurement lit (POAM III), and Stratospheric Aerosol and Gas Experiments II and III (SAGE II and III)] and to finescale tracer fields reconstructed by transporting trace gases based oil MIPAS or climatological data using a reverse-trajectory method. These comparisons confirm the features in the MIPAS data and the interpretation of the evolution of the flow during the vortex decay revealed by those features. Mapped ozone and water vapor from MIPAS and the analyzed isentropic potential vorticity vividly display the vortex breakdown, which occurred earlier than usual. A large tongue of vortex air was pulled out westward and coiled up in an anticyclone, while the vortex core remnant shrank and drifted eastward and equatorward over the South Atlantic. By roughly mid-November, the vortex remnant at 10 mb had shrunk below scales resolved by the satellite observations, while a vortex core remained in the lower stratosphere.
Keywords: Antarktis; klimatologi; meteorologi; polarvirvelen; stratosfæren

The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Accumulation variability derived from an ice core from coastal Dronning Maud Land, Antarctica - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Winther, Jan-Gunnar; Kohler, Jack; Godtliebsen, Fred; Olsen, Lena Ringstad; Hofstede, Coen M.; Van Den Broeke, Michiel R.; Van De Wal, Roderik S. W.; Gundestrup, Niels (Annals of Glaciology, 2004)
A 100 m long ice core was retrieved from the coastal area of Dronning Maud Land (DML), Antarctica, in the 2000/01 austral summer. The core was dated to AD 1737 by identification of volcanic horizons in dielectrical profiling and electrical conductivity measurement records in combination with seasonal layer counting from high-resolution oxygen isotope (δ18O) data. A mean long-term accumulation rate of 0.29 ma–1w.e. was derived from the high-resolution δ18O record as well as accumulation rates during periods in between the identified volcanic horizons. A statistically significant decrease in accumulation was found from about 1920 to the present. A comparison with other coastal ice cores from DML suggests that this is a regional pattern.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi

Description and evaluation of the bergen climate model: ARPEGE coupled with MICOM - Furevik, Tore; Bentsen, Mats; Drange, Helge; Kindem, I. K. T.; Kvamstø, Nils Gunnar; Sorteberg, Asgeir (Climate Dynamics, 2003)
A new coupled atmosphere–ocean–sea ice model has been developed, named the Bergen Climate Model (BCM). It consists of the atmospheric model ARPEGE/IFS, together with a global version of the ocean model MICOM including a dynamic–thermodynamic sea ice model. The coupling between the two models uses the OASIS software package. The new model concept is described, and results from a 300-year control integration is evaluated against observational data. In BCM, both the atmosphere and the ocean components use grids which can be irregular and have non-matching coastlines. Much effort has been put into the development of optimal interpolation schemes between the models, in particular the non-trivial problem of flux conservation in the coastal areas. A flux adjustment technique has been applied to the heat and fresh-water fluxes. There is, however, a weak drift in global mean sea-surface temperature (SST) and sea-surface salinity (SSS) of respectively 0.1 °C and 0.02 psu per century. The model gives a realistic simulation of the radiation balance at the top-of-the-atmosphere, and the net surface fluxes of longwave, shortwave, and turbulent heat fluxes are within observed values. Both global and total zonal means of cloud cover and precipitation are fairly close to observations, and errors are mainly related to the strength and positioning of the Hadley cell. The mean sea-level pressure (SLP) is well simulated, and both the mean state and the interannual standard deviation show realistic features. The SST field is several degrees too cold in the equatorial upwelling area in the Pacific, and about 1 °C too warm along the eastern margins of the oceans, and in the polar regions. The deviation from Levitus salinity is typically 0.1 psu – 0.4 psu, with a tendency for positive anomalies in the Northern Hemisphere, and negative in the Southern Hemisphere. The sea-ice distribution is realistic, but with too thin ice in the Arctic Ocean and too small ice coverage in the Southern Ocean. These model deficiencies have a strong influence on the surface air temperatures in these regions. Horizontal oceanic mass transports are in the lower range of those observed. The strength of the meridional overturning in the Atlantic is 18 Sv. An analysis of the large-scale variability in the model climate reveals realistic El Niño – Southern Oscillation (ENSO) and North Atlantic–Arctic Oscillation (NAO/AO) characteristics in the SLP and surface temperatures, including spatial patterns, frequencies, and strength. While the NAO/AO spectrum is white in SLP and red in temperature, the ENSO spectrum shows an energy maximum near 3 years.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; polarområdene

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Rapid climate shifts in the southern African interior throughout the Mid to Late Holocene - Lee-Thorp, Julia; Holmgren, Karin; Lauritzen, Stein Erik; Linge, Henriette; Moberg, Anders; Partridge, Timothy C; Stevenson, Chris; Tyson Peter D. (Geophysical Research Letters, 2001)
A detailed climate proxy record based on δ18O, δ13O, and grey index of a well-dated stalagmite from Cold Air Cave in the Makapansgat Valley of north-eastern South Africa suggests that regional precipitation, temperatures and vegetation oscillated markedly and rapidly over the last ∼6500 years on centennial and multi-decadal scales. The mid-Holocene prior to 5200 years ago was humid and warm. A fundamental transition occurred 3200 years ago, leading to drier and cooler conditions that culminated at 1750 AD. Comparisons with ice core records suggest synchronous changes implicating rapid global teleconnections.
Keywords: Antarktis; arkeologi; geografi; geologi; klimaendringer; klimatologi; paleontologi

Spatial gradients in snow layering and 10 m temperatures at two EPICA-Dronning Maud Land (Antarctica) pre-site-survey drill sites - Holmlund, P.; Gjerde, K.; Gundestrup, N.; Hansson, M.; Isaksson, E.; Karlöf, L.; Nman, M.; Pettersson, R.; Pinglot, F.; Reijmer, C. H.; Stenberg, M.; Thomassen, M.; et al. (Annals of Glaciology, 2000)
During the 1997/98 field season, Sweden, Norway and The Netherlands performed a pre-site survey for EPICA in Dronning Maud Land, Antarctica. This paper summarizes the results and pays special attention to the high spatial gradients found in snow layering and temperatures. The sites were "Camp Victoria" (CV) on Amundsenisen (76° S, 8° W; 2400 m a.s.l.), approximately 550 km from the coast, and "Camp Maudheimvidda" (CM) on Maudheimvidda (74° S 13° W; 362 m a.s.L), some 140 km from the coast.The drilling programme included both medium-long firn/ice cores and shallow firn cores. These were analysed by means of δ18O, DEP, ECM,β activity, density, and ion content. The combined results suggests a mean annual accumulation rate of 60 mm. we. for CV and 220 mm. we. for CM.Variability measurements of spatial snow layering were performed at two scales; over tens of kilometres by radar and over a few metres by pits and high-resolution radar soundings. Results, as measured by relative standard deviation, were typically 10% on the polar plateau and as high as 50% near the coast.The 10 m temperature measurements were –38.5°C (std dev. = 0.5°) for CV and –17.6°C (std dev.=0.15°) for CM.Snow chemistry was sampled at each medium-long-core drill site. Comparison of δ18O profiles from snow pits and the uppermost part of the CV medium-long core showed large variations. Mean δ18O valuesover 2 m profiles varied between 41.6%, and 39.7%o within a horizontal distance of 50 m.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling